Analisis Faktor–Faktor yang Memengaruhi Ketepatan Waktu Penyajian Laporan Keuangan - Mega Nova Kristiana; Dewi Kusumowati (Jurnal Akuntansi dan Perpajakan, 2019)
This study aims to analyze the factors that influence the timeliness of financial statement presentation in banking companies listed on the Indonesia Stock Exchange. The factors tested in this study are company size, profitability, audit opinion and quality of KAP as independent variables while timeliness as the dependent variable. The research sample consisted of 99 banking companies listed on the Indonesia Stock Exchange (IDX) and submitted financial statements for the period 2015-2017. The data used in this method is secondary data and sample selection using the purposive sampling method. The analytical tool used is logistic regression analysis at a significant level of 5%. The results of hypothesis testing indicate that audit opinions have a significant effect on the timeliness of financial statement presentation, while firm size, audit opinion and KAP quality do not affect the timeliness of financial statements presentation of banking companies listed on the Indonesia Stock Exchange.